014 Match injury incidence: comparisons between team and individual in rugby union. (3rd March 2020) - Bitchell, Leah; Robinson, Gemma; Stiles, Victoria; Mathema, Prabhat; Moore, Isabel
Abstract : Background: Rugby Union has high injury incidence when compared to other professional team sport, with injury rates consistently presented on a group-level. Although group-analysis can provide information on the overall risk for injury within the sport, calculating exposure and number of injuries on a group-level could mask the risk of injury to an individual. Objective: To determine the overall and individual match injury incidence within professional Rugby Union players over three seasons. Design: Descriptive, longitudinal. Setting: Welsh professional regional male Rugby Union. Participants: All first team players of the four Welsh regional Rugby Union teams. Main outcome measures: All time-loss injuries sustained between 1st July 2016 and 30th June 2019. Match exposure (accumulated hours) was quantified from global positioning systems (GPS) for each player during the same time period. Overall and individual match injury incidence (injuries/1000 hours) were calculated across three seasons and for each season separately. Results: A total of 181 players (58%) sustained 675 injuries. Across the three seasons, the overall match injury incidence was 120.4 injuries/1000 match hours (range between seasons: 115.5 to 141.3 injuries/1000 match hours). The individual match exposure ranged from 1 to 91 hours. The individual injury incidence ranged from 22.7 to 1016.2 injuries/1000 match hours. Of the 181 players, 57% had an injury incidence above the overall injury incidence. The mean and median injury incidence was 170.0 and 130.5 injuries/1000 match hours, respectively. Conclusion: The large range of the individual injury incidence shows the potential for group-level analysis to mask the variability that exists for injury rates within a team. Additionally, over half of the players demonstrated an injury incidence above the injury incidence calculated for the team across three seasons. Future work should look further into the differences between individuals who have high and low injury incidence.